Rapamycin, a mTOR inhibitor, induced growth inhibition in retinoblastoma Y79 cell via down-regulation of Bmi-1 - Wang, Yan-Dong (Int J Clin Exp Pathol, 2015)
Rapamycin is useful in the treatment of certain cancers by inhibiting mTOR(mammalian target of rapamycin) pathway. Here, anticancer activity and its acting mechanisms of rapamycin were investigated in human retinoblastoma Y79 cells. CCK-8 assay showed that the IC50 value of rapamycin against human retinoblastoma Y79 cells was 0.122 ± 0.026 μmol/L. Flow cytometry analysis indicated that rapamycin induced G1 cell cycle arrest. Western blot assay demonstrated that the mTOR pathway in Y79 cells was blocked by rapamycin. Western blot and RT-PCR assay showed that Bmi-1 was downregulated in protein and mRNA level by rapamycin treatment. Further Western blot and RNA interference assays showed that rapamycin-mediated downregulation of Bmi-1 induced decreases of cyclin E1, which accounted for rapamycin-mediated G1 cell cycle arrest in human retinoblastoma cells. Together, all these results illustrated that rapamycin induced growth inhibition of human retinoblastoma cells, and inactive of mTOR pathway and downregulation of Bmi-1 was involved in its action mechanism.